Method of analytical modeling and simulation of technological processes subject to the influence of external factors - Denisova, L A; Komarov, V A; Meshcheryakov, V A (Journal of physics. Conference series, 2022)
The method of analytical modeling and simulation of technological processes is presented, which makes it possible to assess the influence of external factors on the operation of information and control systems. The application of this method to study the process of detecting pipeline defects by vibroacoustic control systems is considered. A mathematical model with automatic selection of the parameters of autocorrelation functions of random disturbances is proposed, which makes it possible to take into account the influence of natural and man-made noises on the detection process. The possibility of modeling the influence of random disturbances on the working processes of technological machines is also considered. The proposed simulation models are of practical value, since they allow one to study virtual prototypes of construction and road-building machinery in various modes and reduce the cost of performing expensive field experiments.